2017
DOI: 10.1246/bcsj.20170036
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Bis(diphenylglyoximato)–Nickel(II) Complex with Varying Alkoxy Chain Lengths

Abstract: Crystal structures of eight derivatives of bis(diphenylglyoximato)–nickel(II), bearing four alkoxy chains of different lengths, were determined by single-crystal X-ray crystallography. Sequential transition of packing structures by chain elongation was observed. The packing structures were typically one-dimensional columnar structure comprising metal wires, herringbone structures, quasi-layered structures and layered structures having an interdigitation of alkyl moieties in the alkoxy chains. Each structural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…3 However, four paranormal-alkoxy (-OCmH2m+1) substitutions specifically demonstrated that the columnar geometries comprising linear metal nickel wires were broken by increasing interactions between alkoxy chains in the solid state (m ≥ 4). 4 Since crystallographic studies show that para-buthoxyl (m = 4) substituted compounds exhibit polymorphism when Ni-Ni interactions are quenched, these para-substitution effects without the assistance of long alkoxy chains interactions deserve a consideration. Accordingly, we analyzed the single-crystal structure of the title compound ( Fig.…”
Section: Derivatives Of Bis(diphenylglyoximato)-dmentioning
confidence: 99%
See 2 more Smart Citations
“…3 However, four paranormal-alkoxy (-OCmH2m+1) substitutions specifically demonstrated that the columnar geometries comprising linear metal nickel wires were broken by increasing interactions between alkoxy chains in the solid state (m ≥ 4). 4 Since crystallographic studies show that para-buthoxyl (m = 4) substituted compounds exhibit polymorphism when Ni-Ni interactions are quenched, these para-substitution effects without the assistance of long alkoxy chains interactions deserve a consideration. Accordingly, we analyzed the single-crystal structure of the title compound ( Fig.…”
Section: Derivatives Of Bis(diphenylglyoximato)-dmentioning
confidence: 99%
“…3,4 The title compound was identified by elemental analysis, as follows: Anal. found: C, 6,7 respectively, by the dual-space algorithm before being expanded by Fourier techniques.…”
Section: Derivatives Of Bis(diphenylglyoximato)-dmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the structures of alkyl derivatives vary depending on the chain length. Accordingly, the alkylation of rigid molecules can alter their physical properties [1][2][3][4][5][6][7][8][9][10][11] significantly, including their thermal properties, [12][13][14][15] crystal structure, [16][17][18][19][20][21] and the structure of adsorbed monolayers. [22][23][24][25][26][27][28] We have analyzed the thermal properties of salen derivatives bearing alkyl chains of variable length and found that those with alkoxy groups adopt a liquid crystalline state at varying temperatures depending on the alkyl chain length.…”
Section: Introductionmentioning
confidence: 99%